Initial Growth of Single-Crystalline Nanowires: From 3D Nucleation to 2D Growth - Li, GH (Springer, 2010)
The initial growth stage of the single-crystalline Sb and Co nanowires with preferential orientation was studied, which were synthesized in porous anodic alumina membranes by the pulsed electrodeposition technique. It was revealed that the initial growth of the nanowires is a three-dimensional nucleation process, and then gradually transforms to two-dimensional growth via progressive nucleation mechanism, which resulting in a structure transition from polycrystalline to single crystalline. The competition among the nuclei inside the nanoscaled-confined channel and the growth kinetics is responsible for the structure transition of the initial grown nanowires.